Cannabis use disorder, synthetic cannabinoid and amotivational syndrome: a case report - Akpınar, Abdullah; Demirci, Kadir; Didin, Ekrem; Demirdaş, Arif (Journal of Dependence, 2015)
Cannabis is one of the most widely used substances in the world and it can lead to many well-known psychiatric symptoms and disorders. However, cannabis-related amotivational syndrome cases are less known. In this report, a case of an amoti-vational syndrome caused by chronic cannabis use, who switched to synthetic cannabinoids after developing the syndrome, is presented. The awareness of this syndrome in cannabis use disorder is important in terms of function losses, low treatment motivation and compliance are considered.